Zdolność do absorpcji wiedzy w przedsiębiorstwach turystycznych – identyfikacja znaczenia i możliwości pomiaru - Olszewski, Marcin; Bednarska, Marlena (Ekonomiczne Problemy Turystyki Online, 2016)
The knowledge-based view suggests that the extent of knowledge transfer from knowledge generators to knowledge recipients may depend on recipients’ absorptive capacity ie. “ability of a firm to recognize the value of new, external information, assimilate it, and apply it to commercial ends” (Cohen and Levinthal, 1990, p. 128). The lack or insufficiency of absorptive capacity in a firm hinders the ability to recognize the potential of new ideas arising from interaction with other external knowledge generators. The purpose of this article is to identify the importance of the absorptive capacity in tourism industry, as well as methods of its conceptualization and operationalization. The results include systematization of existing research dedicated to absorptive capacity in tourism and propositions of further studies on this subject.